Предмет: Математика,
автор: deniskaromanov
Помогите решить срочно,вот фото
Приложения:
Ответы
Автор ответа:
1
( b + 2d )^3 - b (b-1)^2 = ( 2 + 2 * (-1))^3 - 2( 2-1)^2=
(2-2)^3 - 2 (2-1)^2= 0 - 2 (1)^2 = 0 - 2 = - 2
(2-2)^3 - 2 (2-1)^2= 0 - 2 (1)^2 = 0 - 2 = - 2
Simka1012:
^3 - это в третьей степени, ^2- это во второй степени
Похожие вопросы
Предмет: Математика,
автор: llebed678
Предмет: Русский язык,
автор: paraevasofia54
Предмет: Геометрия,
автор: nakon3909
Предмет: Алгебра,
автор: good2345
Предмет: Биология,
автор: RuslanaGray